LITERATURE REVIEW: PENGARUH KEPERCAYAAN DAN TRADISI PERNIKAHAN DINI TERHADAP KESEHATAN REPRODUKSI WANITA REMAJA - Kirani, Tegma Panca; Yohana, Nining Ni’mah Yohana Ni’mah; Nafiunnisa, Hanifah; Syifa, Meida Arofatus; Zahro, Diva Nafisatuz; Aulia, Nurul (Universitas Negeri Malang, 2024)
Early marriage is a phenomenon at the tip of the iceberg and will continue to occur due to a lack of information and public understanding regarding early marriage and social traditions that affect the reproductive health of young women. This tradition still persists in Indonesia, especially in rural areas because the culture of early marriage is still strong among some people. Indonesia ranks 37th out of 158 countries for the highest rate of child marriage globally and holds the second highest position in ASEAN, after Cambodia. This research was conducted to find out whether the tradition of early marriage has an effect on the reproductive health of young women. The research uses the literature review method, a review of 10 literature and journal articles in accordance with the theory discussed, especially in the areas of “Women's Reproductive Health'' and “Early Marriage''. The research results show that the tradition of early marriage has an effect on the reproductive health of young women. Marriage at a young age is associated with various reproductive diseases in women, including death during childbirth, cervical cancer, and sexually transmitted diseases (STDs). Miscarriage, molar pregnancy, and premature birth can occur at the beginning of marriage because the mother's physical condition is still in the maturation stage and her reproductive organs are not yet fully mature.